1989
DOI: 10.2527/jas1989.67112892x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Parameters among Breeding Soundness Examination Components and Growth Traits in Yearling Bulls

Abstract: Data on breeding soundness examinations (BSE) and performance traits were obtained on 549 yearling beef bulls at the San Juan Basin Research Center, Hesperus, Co from 1976 to 1984. Genetic parameters estimated for components of BSE included percent motility (PMOT), percent primary abnormalities (PPRIM), percent secondary abnormalities (PSEC), percent normal sperm (PNOR), scrotal circumference (SC) and BSE score (BSESC). Performance traits included birth weight, weaning weight, yearling weight and average daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
35
5
4

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 0 publications
13
35
5
4
Order By: Relevance
“…The Society of Theriogenology has a standard breeding soundness evaluation for beef bulls in which scrotal circumference receives considerable emphasis (Smith et al, 1989). This evaluation provides for observations on bulls at 12 mo of age.…”
Section: Results and Dlscusslonmentioning
confidence: 99%
“…The Society of Theriogenology has a standard breeding soundness evaluation for beef bulls in which scrotal circumference receives considerable emphasis (Smith et al, 1989). This evaluation provides for observations on bulls at 12 mo of age.…”
Section: Results and Dlscusslonmentioning
confidence: 99%
“…Selection of bulls for increased scrotal circumference is considered to be the most rapid method to genetically improve inherent fertility in beef cattle. Scrotal circumference is a moderate to highly heritable trait (Bourdon and Brinks, 1986;Smith et al, 1989a;Kriese et al, 1991) that is easily measured (Lunstra, 1982). Research has shown favorable relationships between scrotal circumference and growth and reproductive traits.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown favorable relationships between scrotal circumference and growth and reproductive traits. Scrotal circumference has also been shown to be favorably correlated with seminal measures (Neely et al, 1982;Smith et al, 1989a), whereas a negative correlation has been reported between scrotal circumference and age at puberty of both males and females (Brinks et al, 1978;Lunstra, 1982;Smith et al, 1989b). Measures of reproductive performance after puberty are also favorably affected by increased scrotal circumference of sire (Smith et al, 1989b).…”
Section: Introductionmentioning
confidence: 99%
“…The value and sign of the correlation found at present study were similar to those previously found in pigs by Smith et al (1989). However, as in other previous research, genetic correlations in which seminal traits are involved showed high standard errors due to the low heritability estimates of those traits and the relatively small number of records.…”
Section: Correlations Between Dg and Semen Traitssupporting
confidence: 91%
“…With regard to the latter, some authors have predicted that bulls genetically superior for growth would be expected to sire sons with testicles of larger circumference and with the ability to produce larger quantities of semen (Knights et al, 1984, Smith et al, 1989. This finding is due to the fact that large testicles produce more testosterone that implies higher accessory glands which in turn could produce more seminal plasma.…”
Section: Discussionmentioning
confidence: 99%